Editorial - Oniwide, Oyetola (NIU Journal of Social Sciences; Vol 10 No 2 (2024): NIU Journal of Social Sciences, Vol. 10 No. 2, June 2024, 2024)
This edition of NIU Journal of Social Sciences focuses on Development Administration, Human Reseource Management, Educational Management, Social Psycholophy and Literary Studies. The first part of the Journal addresses issues in Development Administration such as Democratic Consolidation, Sustainable Development, Rural Development and Good Governanace. It is argued in one of the papers that Nigeria needs more responsive and inclusive governance model by promoting the decentralization of power and giving local communities more authority over resources. It is therefore, suggested amongst others, that Nigeria may move toward a future characterized by greater justice and prosperity by tearing down the legacy of the colonial era and supporting grassroots efforts. Restructuring appears to be a concrete way to fulfill the dreams of the people as the country struggles with its developmental obstacles. Papers in the second section are on Human Research Management. One of the papers in this Section reveals that there are gaps in regulatory oversight and enforcement. Inadequate monitoring and supervision can allow malpractices to go unchecked. Insufficient transparency in reporting practices was also identified to hampers stakeholders' ability to assess the performance and integrity of pension fund administrators. It is therefore, recommended that government should empower Pension Commission to summon the Chairmen, Directors or Managers of non-compliant employers and impose severe sanctions on them. Above all, Pension Commission should embrace high level standard of corporate governance. While tapping into global expertise for training and education of staff, systems development, technology and information communication technology. Using Ijebu Metropolis of Ogun State, Nigeria as a case study, one the papers, in the third section on Educational Management, examines Secondary School Students’ Attitude Towards Gender Stereotype. It consequently, recommends that teacher training needs to be conducted in a way that will allow for the promotion of necessary awareness and knowledge about how to reduce gender-stereotypes through classroom teaching and learning. Papers in the fourth section are on Social Psychology. It is revealed in one of the papers in this section that married men's perceptions and knowledge of family planning were significantly influenced by Family Planning Radio Health Messages, but not their attitudes towards the practice. The paper therefore, recommends that Family Planning Radio Health Messages should be refocused to target men not just women alone since men have the headship position to make some decisions in many families in the South-Western part of Nigeria. In last section on Literary Studies, one of the papers examines the extent to which the term “Choreoclecy” can really fare where it concerns esoterically inclined African worship dances with propensity for trance. Using Descriptive Analytical Approach, the study revealed that this term is articulated through the basic principles and formulae that are required to aid easy dissection and analysis of the inherent compositional structures in most worship dances. On the whole, this issue of NIU Journal of Social Sciences features many interesting research papers. Some of these papers are empirical in nature while others have theoretical base. Each of them focuses on one specific social and management problem or the other; trying to proffer solutions to them. Readers are therefore advised to make proper use of the ideas presented by the various authors.